2020
DOI: 10.5603/dk.2020.0023
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about diabetes mellitus among Polish medical students

Abstract: Background. Due to high prevalence of diabetes mellitus all over the world it is essential for students who will become doctors of different specialties to possess a basic knowledge of it in this field. This pilot surveybased study was designed to assess diabetes related knowledge among faculty of medicine students from all of the medical universities in Poland. Materials and methods. Students were invited to fulfill the questionnaire during Students' Diabetology Conference and via the Internet (social media).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The respondents' levels of knowledge varied significantly due to their personal experience of being a diabetic or having a diabetic person in the family. These results correspond with the results of other studies aimed at assessing the awareness of diabetes-related issues among different patient groups [32,33] and in the general population [34,17] in Poland.…”
Section: Discussionsupporting
confidence: 90%
“…The respondents' levels of knowledge varied significantly due to their personal experience of being a diabetic or having a diabetic person in the family. These results correspond with the results of other studies aimed at assessing the awareness of diabetes-related issues among different patient groups [32,33] and in the general population [34,17] in Poland.…”
Section: Discussionsupporting
confidence: 90%
“…In light of the above, there is a need to reinforce the role of obstetricians and midwives as sources of reliable knowledge, which should be reflected in lowering the incidence of some complications during pregnancy. Additionally, as stated by Kwiendacz et al [ 90 ], there is still a need to educate potential doctors in the field of gestational diabetes mellitus more thoroughly, since there are gaps in students’ knowledge related to diabetes. This indicates a need for persistent improvement in spreading diabetology knowledge during medical education in order to more efficiently combat the diabetes epidemic [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as stated by Kwiendacz et al [ 90 ], there is still a need to educate potential doctors in the field of gestational diabetes mellitus more thoroughly, since there are gaps in students’ knowledge related to diabetes. This indicates a need for persistent improvement in spreading diabetology knowledge during medical education in order to more efficiently combat the diabetes epidemic [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants with diabetes did not have different knowledge score compared to those without diabetes, p value = 0.128. On the contrary, Kwiendacz et al study that was conducted on Polish medical students showed that those with T1D obtained the best scores of knowledge [ 24 ]. This discripancy between the two studies can be justified by the differences in sample size and the frequency of participants with diabetes.…”
Section: Discussionmentioning
confidence: 99%